1995
DOI: 10.2105/ajph.85.10.1402
|View full text |Cite
|
Sign up to set email alerts
|

The challenge of defining and counting generalist physicians: an analysis of Physician Masterfile data.

Abstract: OBJECTIVES. The study reviewed methods for measuring the specialty distribution of the US physician workforce. It was hypothesized that current databases and measurement conventions overestimate the number of generalist physicians. METHODS. A descriptive analysis of the American Medical Association (AMA) Physician Masterfile for California was done with different assumptions about the definition of generalists based on primary and secondary specialty information. RESULTS. A rigorous definition of generalist ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(34 citation statements)
references
References 26 publications
0
34
0
Order By: Relevance
“…Primary care physicians in both countries were defined as those who reported their primary specialty area as general practice or family practice. Consistent with previously validated primary care definitions and prevalent practice patterns, general internists in California and emergency family medicine physicians in Ontario were also included [7,8,[47][48][49]. Physicians in either country who reported that the majority of their clinical time was spent in the practice of gastroenterology or who were board-certified gastroenterologists were defined as such.…”
Section: Methodsmentioning
confidence: 99%
“…Primary care physicians in both countries were defined as those who reported their primary specialty area as general practice or family practice. Consistent with previously validated primary care definitions and prevalent practice patterns, general internists in California and emergency family medicine physicians in Ontario were also included [7,8,[47][48][49]. Physicians in either country who reported that the majority of their clinical time was spent in the practice of gastroenterology or who were board-certified gastroenterologists were defined as such.…”
Section: Methodsmentioning
confidence: 99%
“…8 Because providers are legally required to participate in MCARE, the database contains information on all actively practicing physicians. But because participation is costly, physicians who are not actively practicing generally are not represented.…”
Section: Introductionmentioning
confidence: 99%
“…A probability sample of physicians was obtained using the American Medical Association (AMA) Physician Master®le, a continuously updated source of data on all physicians in the United States (Grumbach et al, 1995). Retirees, students, and physicians who were not currently in practice were excluded.…”
Section: Sample and Proceduresmentioning
confidence: 99%